Empowerment of tribal women - Borda, Gomati (New Delhi, 2008)
Gender is one of the most important topics in the field of sociology. From an outside view, the gender relations in the tribal society seems to be relatively egalitarian with women enjoying quite a high social status and economic value compared to their non-tribal counterparts. The freedom of movement from one place to another is perceived as social freedom among the tribal women. This book explores this myth and focus on how gender stratification as well as discrimination is a prominent feature of the patriarchal tribal social structure. It clearly defines the status of tribal women in Jharkhand region and it also discusses the various dimensions of gender stratification in tribal society. This book summarizes the empowerment of tribal women in the light of recent development relating to education, employment and conversion. It enables the reader to undertake a fresh and critical analysis of the whole tribal society.
Keywords: Tribal women